Bahasa Inggris - Irma Yusnia; SB, Nugraheti Sismulyasih (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
Language skills are important for everyone to master because they can improve students' cognitive, social, and character skills, including writing skills. Writing skills include the ability to use linguistic rules properly. Students have difficulty with grammar material such as the use of punctuation and capital letters. The purpose of this research is to develop a story calendar media based on local wisdom to improve the capital letter and punctuation writing skills of third-grade students in terms of design, feasibility, and effectiveness testing. The research used the Borg and Gall model development method in eight stages with third-grade students at SD Negeri Gisikdrono 03 as the subjects. Data collection techniques included non-tests through interviews, observations, questionnaires, documentation, and tests through pre-tests and post-tests. The results showed that the media was classified as highly feasible with a material expert validation score of 93.18%, a media expert score of 98.21%, a teacher response score of 92.5%, and a student response score of 95%. The effectiveness test was assessed using the N-Gain test with a value of 0.6576, which was interpreted as quite effective, and the paired t-test results had a significance value of 0.000 (< 0.05). This shows that the local wisdom-based story calendar media was proven to be very feasible and effective in improving the capital letter and punctuation writing skills of third-grade elementary school students.